HIV infection with viro-immunological dissociation in a patient with polycystic kidney disease: Candidate for transplantation?. (2016) - Colomba, Claudia; Trizzino, Marcello; Gioè, Claudia; Di Bona, Danilo; Mularoni, Alessandra; Cascio, Antonio
Highlights: Autosomal dominant polycystic kidney disease is the most common among inherited cystic kidney diseases. Patients with HIV infection are at risk of developing acute kidney injury and chronic kidney disease. We provide the first report of HIV infection in a patient with polycystic kidney disease. Lymphopenia should not contraindicate kidney transplantation in patients with HIV infection. Abstract: Here we describe the case of a HIV-infected patient with polycystic kidney disease and end stage renal diseases not transplantable due to the persistence of a CD4 count <200 notwithstanding a good virological response to highly active antiretroviral therapy and suggest that such limitation to kidney transplantation in such as cases might be bypassed.